The Business Environment in Southern Africa : Issues in Trade and Market Integration - Summary - World Bank (World Bank, 2012)
This report assesses some of the key barriers to greater trade and factor market integration in the Southern Africa Development Community (SADC). The SADC has been a free trade area since 2008, and has an ambitious agenda for further trade integration. This report assesses the roles that cross-country differences in business environments have had in impeding cross-border trade flows and the cross-border integration of credit markets and the labor market based on the analysis of microeconomic data on firms and households. The aim of the assessment is to help inform the policy and business environment harmonization agenda of the community. The full report discusses and illustrates the use of price data in monitoring intraregional trade integration. The report evaluates the extent of integration of labor markets among members the statistical agencies of which regularly collect the minimum data required for this purpose, which are South Africa, Mauritius, Tanzania, and Zambia. The results show that, although there is considerable integration of South Africa's labor market with many others in the region, the degree of integration is rather low. This reflects the fact that both trade and capital flows are far more restricted in the region than in places where there is greater cross-border labor market integration.